Rich consumers and poor producers: Quality and rent distribution in global value chains - Swinnen, Johan; Vandeplas, Anneleen (International Food Policy Research Institute, 2009)
In recent years, quality standards have become crucial for developing countries’ agricultural production systems in gaining access to high-value markets abroad or at home. High-value supply chains offer opportunities for high profits, but in order to comply with the required standards, suppliers in developing countries often need extensive support from agrifood companies. We use a theoretical model to investigate under which conditions such synergies between suppliers and agrifood companies are sustainable, and how created rents are distributed, in a context of factor market imperfections and weak contract enforcement. We also derive the implications of development.